Isometric embeddings of Riemannian and pseudo-Riemannian manifolds. - Greene, Robert Everist, 1943- (Memoirs of the American Mathematical Society, 1970)
The purpose of this paper is to provide improved results on non-compact manifolds and extensions to isometric embeddings for arbitrary quadratic forms on the tangent bundle of a manifold ("general metrics") and to the local isometric embedding problem